Paraphelliactis tangi n. sp. and Phelliactis yapensis n. sp., two new deep-sea species of Hormathiidae (Cnidaria: Anthozoa: Actiniaria) from a seamount in the tropical Western Pacific - Li, Yang; Xu, Kuidong (Zootaxa, 2016)
Two new species of hormathiid actiniarians, Paraphelliactis tangi n. sp. and Phelliactis yapensis n. sp., are described from a seamount near the Yap Trench in the tropical Western Pacific. Paraphelliactis tangi n. sp. has a thick cuticle, a tuberculated column divisible into scapus and scapulus, a complete fifth cycle of mesenteries, an equal number of mesenteries at the margin and at the limbus, and up to 192 tentacles without aboral mesogloeal thickenings that are hexamerously arranged in six cycles. This species differs distinctly from the three known species of Paraphelliactis by the above mentioned features (vs. an incomplete fifth cycle of mesenteries, usually more mesenteries at the margin than at the limbus, and the tentacles with aboral mesogloeal thickenings). So far, it is the only member of the genus Paraphelliactis found in the Western Pacific. Phelliactis yapensis n. sp. has an asymmetric bilobed oral disc and column, tuberculated scapus and scapulus, an incomplete fifth cycle of mesenteries, and up to 162 tentacles with aboral mesogloeal thickenings that are alternately arranged in two cycles. In comparison with other Phelliactis species, the basitrichs of mesenterial filaments of Ph. yapensis are distinctly larger. Phelliactis yapensis n. sp. is the fourth species of Phelliactis found in the Western Pacific.